Trace element composition of size-fractionated suspended particulate matter samples from the Qatari Exclusive Economic Zone of the Arabian Gulf: the role of atmospheric dust - Oguz Yigiterhan (14151006) (2020)
We analyzed net-tow samples of natural assemblages of plankton, and associated particulate matter, from the Exclusive Economic Zone (EEZ) of Qatar in the Arabian Gulf. Size-fractionated suspended particles were collected using net tows with mesh sizes of 50 and 200 µm to examine the composition of small- and large-size plankton populations. Samples were collected in two different years (11 offshore sites in October 2012 and 6 nearshore sites in April 2014) to examine temporal and spatial variabilities. We calculated the excess metal concentrations by correcting the bulk composition for inputs from atmospheric dust using aluminum (Al) as a lithogenic tracer and the metal∕Al ratios for average Qatari dust. Atmospheric dust in Qatar is depleted in Al and enriched in calcium (Ca), in the form of calcium carbonate (CaCO3), relative to the global average Upper Continental Crust (UCC). To evaluate the fate of this carbonate fraction when dust particles enter seawater, we leached a subset of dust samples using an acetic acid–hydroxylamine hydrochloride (HAc–HyHCl) procedure that should solubilize CaCO3 minerals and associated elements. As expected, we found that Ca was removed in Qatari dust; however, the concentrations (ppm) for most elements actually increased after leaching because the reduction in sample mass resulting from the removal of CaCO3 by the leach was more important than the loss of metals solubilized by the leach. Because surface seawater is supersaturated with respect to CaCO3 and acid-soluble Ca is abundant in the particulate matter, we only used unleached dust for the lithogenic correction. Statistical analysis showed that for many elements the excess concentrations were indistinguishable from zero. This suggested that the concentrations of these elements in net-tow plankton samples were mostly of lithogenic (dust) origin. These elements include Al, Fe, Cr, Co, Mn, Ni, Pb, and Li. For several other elements (Cd, Cu, Mo, Zn, and Ca) the excess concentrations present after lithogenic correction are most likely of biogenic/anthropogenic origin. The excess concentrations, relative to average dust, for most elements (except Cd) decreased with distance from the shore, which may be due to differences in biology, currents, proximity to the coast, or interannual processes. Other Information Published in: Biogeosciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5194/bg-17-381-2020